PSYCHOLOGICAL ANALYSIS OF LITERARY AND EDUCATIONAL VALUE IN THE NOVEL PSYCHOPATH TEST - Hari Kurniawan, Erwin (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This journal explores the relationship between literature and psychology, focusing on Jon Ronson's